Effects of climate change on streamflow in the Dez Basin of Iran using the IHACRES model based on the CMIP6 model - Mohammad Reza Goodarzi; Mohammad Javad Abedi; Majid Niazkar (Journal of Water and Climate Change, 2024)
Understanding the changes in river flow is an important prerequisite for designing hydraulic structures as well as managing surface water resources in basins. By using the LARS-WG statistical downscaling model, the outputs of the general circulation model of the sixth report, including the ACCESS-ESM1 and BCC-CSM-MR models, under the SSP5.8.5 and SSP2.4.5 release scenarios. A more accurate spatial scale and daily precipitation and temperature time series were obtained for the studied area during the period of 2015–2043. Then the Identification of unit Hydrographs And Component flows from Rainfall, Evaporation and Streamflow data (IHACRES) rainfall-runoff model was calibrated in the study area. Based on the fit statistics in the calibration and validation stages, the overall performance of the developed model was evaluated as satisfactory. The calibrated hydrological model was driven by rainfall data and reduced air temperature to predict the effect of climate change on the output of the studied basin. The study showed that the studied basin has more rainfall (on average, 20.8% in the ACCESS-ESM1 model and 33.2% in the BCC-CSM2-MR model). The flow rate of the main river in the ACCESS-ESM1 model will decrease by 15% compared to the base period, and in the BCC-CSM2-MR model, it will increase by 16% compared to the base period. HIGHLIGHTS The LARS-WG statistical downscaling model is used to analyze the outputs of the GCM from the sixth report.; The aim is to assess the performance of the model runoff simulation (IHACRES) under the effect of climate change.; The object is to evaluate the accuracy of the IHACRES modeling in relation to precipitation and temperature parameters in the field of Dez.;